Cosmic love at the multiverse hair salon - Mare, Annie (Ace, 2025)
"A multiverse novel about two women who fall in love despite living in worlds that are five months apart, as they try to find a timeline that doesn't end in disaster, in this debut novel by Annie Mare. Tressa Fay Robeson has never been shy, which is how she's made a name for herself as an in-demand hairstylist and social media star. So she can admit that spending her days at her hair salon and her nights with her tight-knit group of friends (and one grumpy cat) is not the kind of exciting life she'd hoped for. When a misdirected text from a stranger leads to a flirty exchange, she surprises herself by suggesting an impulsive meetup. But the woman, Meryl, never shows. Tressa Fay brushes it off-until Meryl's sister and friend show up at the salon demanding to know what's going on. Because, you see, there's no way Meryl could have texted her. Meryl has been missing for a month. Tressa Fay and her tight-knit group of friends soon discover they aren't dealing with a catfish, but a temporal paradox. As they come to terms with the idea of parallel universes, they realize how many times their paths have crossed like this before. But even as they understand the multiverse more and more, nothing keeps Meryl from vanishing. As it draws closer to the moment of Meryl's disappearance, there's only one question left: Have they done enough to change the outcome, or have they done so much that none of them will make it past that fateful day in September?"--